School effectiveness in marginalized urban settings. Case of a primary school in Monterrey, Mexico - Duarte, José (2021)
This article investigates how institutional management, teacher and family involvement are amalgamated for sustained school achievement. The research took place in a public school in northern Mexico. The students of this institution, -located in a marginalized and violent community, obtained for three years, scores higher than the national average in tests that measure knowledge in Spanish, mathematics, and science. Through a qualitative case study that used organizational microsociology and symbolic interactionism, we found that institutional management is based on organizational systems, leadership is shared and based on trust; the teachers have high academic and pedagogical competencies, use innovative playful strategies, maintain the concern to maintain high academic standards; interpersonal relationships are close; families support and participate in the school on a consistent basis. It is concluded that it is possible to achieve educational effectiveness when the context is not seen as limiting, but as an enhancer of learning, when there is organization, integration, commitment, roots and when the educational community considers that education has the potential for transformation social.